1997
DOI: 10.1182/blood.v90.8.3222
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Multilineage Engraftment of Allogeneic Hematopoietic Stem Cells in NOD/SCID Mice After In Utero Transplantation

Abstract: Substantial barriers exist to the engraftment of hematopoietic cells in mice after in utero transplantation. Although high levels of donor-derived hematopoiesis have been reported in SCID mice, the majority of chimeric recipients exhibit decreasing levels of donor cells over time. To directly test whether the natural killer cell and macrophage activity of the recipients represents a barrier to sustained engraftment, fetal NOD/SCID mice were injected on day 13.5 of gestation with an enriched congenic hematopoie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A second approach may be the in utero injection of human stem cells into NOD-scid mice. It has recently been observed that in utero injection of allogeneic cells into day 13-14 gestation NOD-scid fetuses results in engraftment of the allogeneic stem cells in the absence of irradiation [120]. If the NOD-Rag1 null mice support enhanced human cell engraftment similar to that observed in NOD-scid mice, or if human stem cells can be engrafted in utero without the need for irradiation, two of the major limitations of the hu-SRC-NOD-SCID model would be overcome.…”
Section: Recent Advances In Development Of New Immunodeficient Mice Amentioning
confidence: 99%
“…A second approach may be the in utero injection of human stem cells into NOD-scid mice. It has recently been observed that in utero injection of allogeneic cells into day 13-14 gestation NOD-scid fetuses results in engraftment of the allogeneic stem cells in the absence of irradiation [120]. If the NOD-Rag1 null mice support enhanced human cell engraftment similar to that observed in NOD-scid mice, or if human stem cells can be engrafted in utero without the need for irradiation, two of the major limitations of the hu-SRC-NOD-SCID model would be overcome.…”
Section: Recent Advances In Development Of New Immunodeficient Mice Amentioning
confidence: 99%
“…Of a total of 65 embryos in seven pregnant dams 51 (78%) were injected with human FL cells and 33 (51%) were live‐born. We directly compared these results to those obtained when we transplanted allogeneic lineage‐negative haemopoietic progenitor cells into NOD/SCID recipients in a parallel series of experiments ( Archer et al , 1997 ). Of a total of 84 embryos, in nine pregnant dams, 53 (63%) were injected and 36 pups (43%) were born.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of donor cell engraftment in both mice and humans have been limited to situations in which the recipient has a stem cell or lineage‐specific defect ( Archer et al , 1997 ; Blazar et al , 1995a , b; Howson‐Jan et al , 1993 ; Fleischman & Mintz, 1979). If the defect inhibits stem cell function as in W v mice, enhanced engraftment of normal donor stem cells would be the expected result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Previously, the in utero transplantation of hematopoietic cells led to stable long-term engraftment in the postnatal environment. 14,[16][17][18] In this study, we show for the first time that IUCT in piglets with adult human hepatocytes allows the stable postnatal engraftment of human hepatocytes. The effectiveness of our IUCT step was determined by a cytotoxicity assay that measured the change in piglet serum reactivity to human PBLs after 3 postnatal SQ priming injections using human hepatocytes.…”
Section: Discussionmentioning
confidence: 99%